Why are the unemployed in worse health? The causal effect of unemployment on health - Schmitz, Hendrik (Labour Economics)

Profit efficiency and ownership of German hospitals - Herr, Annika; Schmitz, Hendrik; Augurzky, Boris (Health Economics)

Internationale Publikationen und gute Lehre? Eine Panel-Daten-Analyse wirtschaftswissenschaftlicher Bachelor- und Mastermodule. - Lück, Sonja (Herausforderung Internationalisierung)

International integration and the determinants of regional development in China - Gries, Thomas; Redlin, Margarete (Economic Change and Restructuring)

Stability and Nash implementation in matching markets with couples - Haake, Claus-Jochen; Klaus, Bettina (Theory and Decision)

Survival at the center—the stability of minimum differentiation - Hehenkamp, Burkhard; Wambach, Achim (Journal of Economic Behavior & Organization)

Entrepreneurship and Structural Economic Transformation - Gries, Thomas; Naudé, Wim (Small Business Economics)

Short-run and Long-run Dynamics of Growth,Inequality and Poverty in the Developing World - Gries, Thomas; Redlin, Margarete

On the equivalence of Nash and evolutionary equilibrium in finite populations - Hehenkamp, Burkhard; Possajennikov, Alex; Guse, Tobias (Journal of Economic Behavior & Organization)

Strategic Unemployment - Angerhausen, Julia; Bayer, Christian; Hehenkamp, Burkhard (Journal of Institutional and Theoretical Economics (JITE))

Effizienz Deutscher Krankenhäuser im Zeitablauf - Schmitz, Hendrik; Augurzky, B.

Hochschulforscher oder Hochschullehrer? Eine Panel-Daten-Analyse wirtschaftswissenschaftlicher Bachelor- und Masterkurse - Lück, Sonja (Hochschulmanagement)

Monotonicity and Nash implementation in matching markets with contracts - Haake, Claus-Jochen; Klaus, Bettina (Economic Theory)

DIVIDING BY DEMANDING: OBJECT DIVISION THROUGH MARKET PROCEDURES - Haake, Claus-Jochen (International Game Theory Review)
We discuss a model, in which two agents may distribute finitely many objects among themselves. The conflict is resolved by means of a market procedure. Depending on the specifications, this procedure serves to achieve bargaining solutions such as the discrete Raiffa solution, the Kalai-Smorodinsky solution and the Perles-Maschler solution. The latter is axiomatized using the superadditivity axiom, which in the present context is readily interpreted as resolving a specific source of conflict potential.

Linkages between Financial Deepening, Trade Openness and Economic Development: Causality Evidence from Sub-Saharan Africa - Gries, Thomas; Kraft, Manfred; Meierrieks, Daniel (World Development)

The Optimal Distance to Port for Exporting Firms - Gries, Thomas; Naudé, Wim (Journal of Regional Science)

Explaining Regional Export Performance in a Developing Country: The Role of Geography and Relative Factor Endowments - Gries, Thomas; Naudé, Wim (Regional Studies)

Entrepreneurship and regional economic growth: towards a general theory of start-ups - Gries, Thomas; Naudé, Wim (Innovation: The European Journal of Social Science Research)

Studentische Modulevaluation - Methoden, Ergebnisse und Schlussfolgerungen aus statistischer Sicht - Lück, Sonja

Spieltheoretische Anmerkungen zur Förderung universitärer Spitzenforschung im Rahmen der Exzellenzinitiative - Kraft, Manfred; Brunn, Hans-Georg; Lück, Sonja (Bildungsökonomie in der Wissensgesellschaft)